Antimalarial activities of Diplazium esculentum (RETZ.) SW. Aqueous extract in Plasmodium berghei-infected mice - Md Zulkifli, Nor Zuziana; Ramli, Norazsida; Othman, Muhammad Zulhilmi; Shafiq Zawawi, Nur Hafiz; Baba, Mohd Shukri (IIUM Press, 2021)
Antimalarial drug resistance is a threat to the worldwide effort to control and eliminate malaria and warrants the need to discover new drugs for malarial infection. Thus, this study aims to evaluate the antimalarial activity of Diplazium esculentum aqueous extract in Plasmodium berghei-infected mice. Forty-two mice were divided into seven groups and the extract was given orally to all treatment groups. The preventive groups (G1 and G2 groups) were given 100 mg/kg of extract 19 days and eight days before infection respectively. Meanwhile, the curative groups were given extract on the same day of infection (G4 group) and four days after infection (G5 group) at different doses, 100 mg/kg and 400 mg/kg respectively. G3 and G5 were the positive control group for each of the treatment that was given primaquine and chloroquine, respectively. All mice were observed for parasitemia level, mortality and body weight changes. For preventive treatment, the plant extract that was given 19 days before infection was found to reduce the parasitemia by 2.67%. Curative treatment showed that the effective dose was found to be 100 mg/kg, which reduced parasitemia by 1.83%. In conclusion, D. esculentum extract showed preventive properties but no curative properties. This result indicates that D. esculentum could not be compared with commercial antimalarial drugs.